Avaliação anticancerígena de nanoemulsões contendo r-(-)- carvona - Gabínio, Brennda Martins (2019)
Characterized by a hyperproliferative disorder, cancer remains one of the leading causes of death worldwide. Where, breast cancer proves to be the most common and lethal among the female population in which even after treatment, many patients have deficiencies in physical and cognitive functioning, side effects that are often related to formulations administered during treatment. Showing that current therapies combine treatment with a high degree of uncertainty. Carvone is a monoterpene naturally found in several essential oils that in recent studies caused induction of apoptosis, inhibition of migration and arrest of the cell cycle in tumor cells presenting little or no toxicity in normal cells, however, it is characterized as volatile, presenting low solubility in water and inadequate biocompatibility in the form of native oil, therefore needing a transporter to efficiently reach cancer cells. Among the delivery systems, there are nanoemulsions that are emulsions of submicron size and systems used for systemic delivery of biologically active agents. Thus, the present study aimed to evaluate the in vitro anti-cancer potential of R - (-) - free and nanoencapsulated carvone on breast cancer cell culture. The nanoemulsions were produced in concentrations of 5mg / mL, 12.5 mg / mL, 25 mg / mL, 37.5 mg / mL and 50 mg / mL by the ultrasonic emulsification method and characterized by of their physical-chemical aspects, determining the particle size, polydispersity index and zeta potential, in addition to obtaining the calibration curve and the pH and conductivity values. In vitro cytotoxicity tests were also performed on the fibroblast (L929) and mammary gland (4T1) lines, measuring cell viability using the MTT reduction test and we performed the wound healing test observed at 0h, 24h and 72h. The results found show nanoparticles with average size varying between 133nm and 183nm, not proportional to the amount of drug used, average zeta potential of -36.4mV and polydispersion index less than 0.240. Vehicle toxicity was the next control group and showed values above 100%, inducing possible proliferation. The emulsions analyzed were cytotoxic for the breast cancer lineage, where the nanosystem shows good activity and potential for potentiation of cytotoxic effects when compared with a free R-CV. The results shown a fast migration in the control group, with the permanence of the migration potential with the free drug and alteration in the adhesion of the matrix cell in cancer cells. Therefore, we achieved satisfactory formulation with a significant anticancer effect on breast cancer cells in a short period of time, showing represents a promising formulation to assist the conventional treatments used for this disease.